Investigating Effect of Sodium Methabisulfite Concentrations on Chemical Properties and Color of Avocado Seed Starch - Sari, Putri Meutia; Muhardina, Virna; Rahmiati, Tengku Mia; Irmayanti, Irmayanti; Anwar, Chairil (Serambi Journal of Agricultural Technology, 2025)
Avocado seeds have potential as an alternative source of starch; however, the color and quality of the starch are often affected by the extraction process. This study aims to investigate the effect of various concentrations of sodium metabisulfite on the yield, moisture content, ash content, as well as the preference and descriptive evaluation of the color of avocado seed starches. The research conducted using a Completely Randomized Design (CRD) with non-factorial treatment levels of sodium metabisulfite concentrations at 0.05%, 0.1%, 0.15%, and 0.2%, each repeated five times. The results established that sodium metabisulfite concentrations have not significantly affected starch yield or color preferences, but it had a significant effect on moisture content, ash content, and color descriptions of the starch. Increasing concentrations of sodium metabisulfite consistently increased moisture and ash contents while reducing browning intensity, as indicated by a decrease in color scores from light-dark brown at 0.05% concentration to light cream at 0.20%. In conclusion, sodium metabisulfite plays a role in modifying the moisture and ash content as well as the color of avocado seed starch without significantly altering the extraction yield and color preferences